WEAR AND CORROSION PERFORMANCES OF NEW FRICTION MATERIALS FOR AUTOMOTIVE INDUSTRY - (:unkn) unknown (CROATIAN METALLURGICAL SOC, 2012)
In this study, after a NiCr bond layer was deposited on a pearlitic, grey cast iron rotor disc of the kind used in a production passenger car (Toyota Corolla 1600 cc), Cr3C2-NiCr and Al2O3-TiO(2)powders were sprayed using High Velocity Oxygen Fuel(HVOF) and plasma spray processes, respectively. The discs were subjected to cosmetic corrosion test according to SAE J2334 test standard. Additionally, wear tests were carried out using a reciprocating wear tester by rubbing a 10 mm diameter Al2O3 ball on the specimens machined from rotor discs in salt solution. It was found that the Cr3C2-NiCr coating (HSCN) sprayed using HVOF method exhibited highest hardness and highest corrosion and wear resistances.
Keywords: wear; friction; corrosion; friction material; coating; automotive industry; BEHAVIOR; IRON